KARAKTERISTIK FOTO TORAKS PADA ANAK USIA 1 BULAN - 17 TAHUN DENGAN DIAGNOSA TUBERKULOSIS PARU DI RS HAJI MEDAN - KHOFIFA RAHMA; EKA AIRLANGGA (JURNAL ILMIAH KOHESI, 2021)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Pulmonary TB in children in Indonesia isstill undetected due to the difficulty of diagnosing pulmonary TB in children. Chest X-ray is one modality that is often used tohelp diagnose tuberculosis in children according to the Indonesian Pediatric Association scoring system. To find out thecharacteristics of the chest X-ray in children diagnosed with pulmonary tuberculosis. This study used a descriptive method,data were obtained using rectrospective data of pediatric pulmonary tuberculosis in 2017, 2018 and 2019 using simplerandom sampling technique. The number of children with pulmonary tuberculosis in Haji Medan Hospital was 122 patientsafter being randomized simply and according to the inclusion criteria as many as 62 patients. Characteristics of pediatricpulmonary tuberculosis patients based on sex were mostly male, amounting to 37 patients (59.7%), the most age was 1month - 5 years old, amounting to 37 patients (59.7%). Most nutritional status in malnutrition amounted to 24 patients(38.7%). The characteristics of the chest X-ray based on the type of lesion most of the infiltrates lesions were 36 patients(58.1%), with the location of the lesions in both lungs, namely the right and left lungs, amounting to 38 patients (61.3%), andthe maximum lesion area was 38 patients (61.3%) and most the sample had no complications totaling 60 patients (96.8%).Male gender, age 1 month-5 years, poor nutritional status, with chest X-ray infiltrates lesion type, maximal lesion area,location of lesions in both lungs, and no complications.